2021
DOI: 10.3389/fphys.2021.667024
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the Lipid Profile and the Desaturases Activity in Patients With Severe Pneumonia by SARS-CoV-2

Abstract: The kidnapping of the lipid metabolism of the host’s cells by severe acute respiratory syndrome (SARS-CoV-2) allows the virus to transform the cells into optimal machines for its assembly and replication. Here we evaluated changes in the fatty acid (FA) profile and the participation of the activity of the desaturases, in plasma of patients with severe pneumonia by SARS-CoV-2. We found that SARS-CoV-2 alters the FA metabolism in the cells of the host. Changes are characterized by variations in the desaturases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Interestingly, a study in elderly patients showed a lower metabolic flux in the fatty acid pathway in survivors vs the deceased [ 81 ]. A more detailed analysis at the level of a single fatty acid showed opposite changes in levels of different fatty acids in serum of patients with severe COVID-19 depending on the type of the fatty acid and its desaturation index [ 82 ]. For example, the palmitic and stearic acid, needed for the formation of viral membranes, were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study in elderly patients showed a lower metabolic flux in the fatty acid pathway in survivors vs the deceased [ 81 ]. A more detailed analysis at the level of a single fatty acid showed opposite changes in levels of different fatty acids in serum of patients with severe COVID-19 depending on the type of the fatty acid and its desaturation index [ 82 ]. For example, the palmitic and stearic acid, needed for the formation of viral membranes, were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…However, more investigations are necessary to verify this hypothesis. In addition, the alterations in the glucose-insulin axis and FA metabolism [48] may lead to an increase in OS, increased inflammation, interleukin storm, and decreased mobilization of leukocytes, phagocytic activity, TAC and impairment of endothelial function [52]. In this sense, it has been reported that the TAC levels were considerably lower in serum of mild and severe COVID-19 patients in comparison with control subjects [53].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia, hyperinsulinemia and IR contribute to increase ROS that attack free fatty acid (FFA) or esterified arachidonic acid in the phospholipids of the membrane and constitute conditions that are frequently found in COVID-19 and in patients with MS. Hyperglycemia, hyperinsulinemia and IR increase the rate of lipolysis which is accompanied with liberation of FFA to the circulation. An increased fatty acid (FA) metabolism is essential for the formation of the viral membranes including those of SARS-CoV-2 [48]. Furthermore, the increase in FFA and the alteration in FA metabolism increase gluconeogenesis, reduce β-cells mass and provide substrates for the synthesis of triglycerides that are elevated in COVID-19 patients [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been reported that SARS-CoV-2 may alter fatty acids metabolism. These changes are characterized by alterations of the fatty acid desaturase enzyme that leads to variations in the phospholipids and nonesterified fatty acid profiles [ 44 ]. We propose that SARS-CoV-2 may induce or hasten progression of MAFLD towards a more severe disease state, making this condition a true phenotype of PACS.…”
Section: Discussionmentioning
confidence: 99%